IMPLEMENTASI KENYAMANAN TERMAL: HASIL PEMETAAN AREA DAN REKOMENDASI DESAIN LANSKAP REKREASI PANTAI PULAU KODOK TEGAL - Putri, Balqis Taqiya; Besila, Qurrotu Aini (Universitas Trisakti, 2023)
Thermal comfort is one of the factors that humans feel when they are outdoors due to human activities. Pulau Kodok Beach of Tegal City, has a hot climate. From these problems, the thermal comfort conditions need to be studied through research to find out how the thermal comfort conditions are and their implementation in landscape design. The research method used is descriptive quantitative, where the aspects of thermal comfort that are measured are air temperature, humidity, and wind speed. These measurements were assessed through analysis of the Temperature-Humidity Index (THI) and the Beaufort scale. The results obtained are that the thermal comfort conditions at Pulau Kodok Beach are not comfortable, which is shown through a map of the distribution of thermal comfort in the morning, afternoon, and evening. These results are implemented in recreational landscape design as a form of problem-solving that is expected to meet the needs of outdoor human activities. The condition of thermal comfort in an area is influenced by the physical and climatic conditions of the environment, so in solving the problem each has its criteria and is adjusted to human needs. In this case, the recreational landscape design plays an important role in the sustainability of the beach recreation area.